IMPLEMENTASI PRINSIP ISLAM DALAM AKTIVITAS EKONOMI: ALTERNATIF MEWUJUDKAN KESEIMBANGAN HIDUP - Suhadi, Mursal dan (Jurnal Penelitian, 2015)
IMPLEMENTING ISLAMIC PRINCIPLE IN ECONO- MIC ACTIVITIES: ALTERNATIV TO REALIZE THE LIFE BALANCE. This paper aims to explain the principles of Islam in economic activity contained in the al-Quran and Hadith. The principle of  balance occupy a decisive role in human life to reach al-Falah. The balance is the Sunnah of  Allah, balanced life is one of  the essence of  Islam, so Muslims were referred to as the people of the middle (Ummatan wasthan). Islamic Economics aims to create a balanced life, which includes, among others, the physical with the mental balance, the material with the spiritual, the individual with the social, the present with the future, and the world to the hereafter. This is because, physical balance with mental, spiritual or the material will create a holistic for the welfare of man. Economic development are too concerned with material aspects and ignore the spiritual aspect only will bear false happiness, even quite disastrous.keyword: Islam, Economic, Balanced.Tulisan  ini  bertujuan  untuk  menjelaskan  tentang  prinsip  Islam dalam aktivitas ekonomi yang tertuang dalam al-Quran dan Hadis. Prinsip keseimbangan menduduki peran yang sangat menentukan dalam kehidupan manusia untuk mencapai al-Falah. Keseimbangan merupakan sunnah Allah, kehidupan yang seimbang merupakan salah satu esensi ajaran Islam, sehingga umat Islam pun disebut sebagai umat pertengahan (Ummatan wasthan). Ekonomi Islam bertujuan untuk menciptakan kehidupan yang seimbang, yang mencakup antara lain keseimbangan fisik dengan mental, material dengan spiritual, individu dengan sosial, masa kini dengan masa depan, serta dunia dengan akhirat. Hal ini karena, keseimbangan fisik dengan mental, atau material dengan spiritual akan menciptakan kesejahteraraan  holistik  bagi  manusia.  Pembangunan  ekonomi yang terlalu mementingkan aspek material dan mengabaikan aspek spiritual hanya akan melahirkan kebahagiaan semu, bahkan justru menimbulkan petaka.keywords: Islam, Ekonomi, Keseimbangan